Multimodel-Based Learning Strategy And Wetland Environment-Based Learning Approach: Alternative Solution to train Higher Order Thinking Skills - Abdul Salam; Sarah Miriam; Muhammad Andrean Lazuardi; Norhalimah Norhalimah; Syah Warunadwipa Andiantosa (Universitas Lambung Mangkurat, 2022)
A number of studies on multimodel-based learning strategy and environment-based learning approaches have been proven effective in improving learning outcomes. This study seeks to combine the strategy and the approach to train higher-order thinking skills as one of the 21st Century skills. This quasi-experiment study used one group pretest and post-test design. Data was collected using essay tests. The results showed that multimodel and wetland environment-based learning effectively improves students' higher-order thinking skills with a gain score of 0.63 (medium category). This study indicates the importance of integrating practicum activities and theory in learning in the classroom so that students' learning motivation is maintained and higher-order thinking skills are continuously trained.